A social study of the technicians dealing with refrigerant gases: Diagnosis of the behaviours, knowledge and importance attributed to the F-gases. (February 2023) - Martinho, Graça; Castro, Paulo J.; Santos, Pedro; Alves, Ana; Araújo, João M.M.; Pereiro, Ana B.
Highlights: Technicians play an important role in the sustainability of the refrigeration sector. Technicians' behaviour was assessed to improve policy regulatory F-gases strategies. Their level of knowledge about F-gases is not as high as would be expected. The selective collection of waste containing F-gases is imperative and necessary. Awareness campaigns need to be reinforced to promote appropriate behaviour. Abstract: Compliance with the international agreements and regulations aiming at mitigating emissions of gases with high global warming potential (GWP) requires the involvement of all stakeholders in the value chain of equipment containing refrigeration gases. In particular, the technicians dealing with the installation, maintenance, and dismantling of refrigeration equipment have a relevant role in the prevention of the release of refrigerant gases and their correct management. Besides technical information and training, the awareness of these technicians about the effects of fluorinated gases (F-gases) on global warming is critical for policy, regulations and strategies related to F-gases. This work presents the results of a questionnaire conducted with 586 Portuguese, Spanish, and French technicians to diagnose their behaviours, knowledge, and risk perception face to refrigeration gases and global warming. The results reveal that the repaired equipment mostly contains the pure HFCs R-32 and R-134a, the HFC blends R-410A, R-407C, and R-404A, and the fourth-generation HFCHFO blend R-449A. They also indicate the need to implement more efficient and credible information/awareness campaigns and to improve the training of these professionals in key respects, such as the relation between F-gases and climate change and the importance of their individual responsibility. Several suggestions were provided by the inquired technicians to improve the repair/maintenance process aiming at mitigating the effect of refrigeration gases on climate change, and to improve the awareness of this topic. These suggestions should be taken into consideration to improve legislation and policies.